In vivo Imaging of Mitochondrial Transport in Single-Axon Regeneration of Zebrafish Mauthner Cells - Xu, Yang; Chen, Min; Hu, Bingbing; Huang, Rongchen; Hu, Bing (Frontiers in Cellular Neuroscience, 2017)
Mitochondrial transport is essential for neuronal function, but the evidence of connections between mitochondrial transport and axon regeneration in the central nervous system (CNS) of living vertebrates remains limited. Here, we developed a novel model to explore mitochondrial transport in a single Mauthner axon (M axon) of zebrafish with non-invasive in vivo imaging. To confirm the feasibility of using this model, we treated labeled zebrafish with nocodazole and demonstrated that it could disrupt mitochondrial transport. We also used two-photon laser axotomy to precisely axotomize M axons and simultaneously recorded their regeneration and the process of mitochondrial transport in living zebrafish larvae. The findings showed that the injured axons with stronger regenerative capability maintain greater mitochondrial motility. Furthermore, to stimulate axon regeneration, treatment with dibutyryl cyclic adenosine monophosphate (db-cAMP) could also augment mitochondrial motility. Taken together, our results provide new evidence that mitochondrial motility is positively correlated with axon regeneration in the living vertebrate CNS. This promising model will be useful for further studies on the interaction between axon regeneration and mitochondrial dynamics, using various genetic and pharmacological techniques.